Axiomatic design approach to finite-time thermodynamic analysis of stirling heat engine - Piroğlu, Serdar (My University, 2003)
Bu tez çalısmasında, mevcut araştırmalarda varolan Stirling tipi ısı makinasının Sonlu Zamanlı Termodinamik modeli alınarak Aksiyomatik Tasarım'ın Bagımsızlık Aksiyomu yardımıyla, parametrik değerlerinin hangi çalışma aralıklarında Aksiyomatik Tasarıma göre iyi bir tasarım olduğu incelenmiştir. Bu tezde Sonlu Zamanlı Termodinamik yardımıyla hesaplanan güç ve ısıl verim Aksiyomatik Tasarım kurallarına göre Fonksiyonel Gerekler olarak tanımlanarak inceleme yapılmıştır. Bu tez çalışmasındaki Stirling tipi ısı makinası, mükemmel olmayan bir rejeneratör içermektedir. Ayrıca termal ısı kaynağı ve ısı yutucusu sonlu bir kapasiteye sahiptir. Buna ek olarak çevreye direkt ısı kaybı vardır. Bu model için Fonksiyenel Gerekler (FG) ve Tasarım Parametreleri (TP) hesaplanmıştır. FG ve TP leri bağlayan Tasarım matrisinin elemanları yoluyla elde edilen Diklik ve Parelellik Kavramları yoluyla Tasarım Parametrelerinin hangi çalışma aralıklarında daha iyi bir tasarım elde edilebileceği incelenmiş ve TP uzayında grafiklerle ortaya konulmuştur. 24.09.2003 Serdar PİROĞLU In this thesis existing FTT models of the Stirling heat engine from the open literature had been taken and Independence Axiom together with Reangularity and Semangularity concepts from the Axiomatic Design have been utilized in order to determine the regions in working space where the behavior of Stirling engine shows uncoupled or at least decoupled behavior. In this thesis, finite time thermodynamics has been applied to obtain the power output and the corresponding thermal efficiency of an irreversible Stirling heat engine with internal heat loss in the regenerator and for the finite heat capacity of the external reservoirs. Power output and thermal efficieny are taken as Functional Requirement (FR). Engine parameters are taken as Design Parameters (DP). Utilizing the elements of the Design Matrix, Reangularity and Semangularity equations had been derived and calculated within the parameters limits. Contours of FRs, Semangularity and Reangularity have been plotted on DPs domain to visualize the regions where the Independence Axiom is satisfied for a better design. 24.09.2003 Serdar PİROĞLU
Keywords: Makine Mühendisliği